IDENTIFIKASI MOTIVASI PETANI DALAM MELAKUKAN USAHATANI TEMBAKAU DI KABUPATEN SITUBONDO - Puryantoro Puryantoro; Fathor Rozy (Universitas Galuh Ciamis, 2020)
One of the plantation crops that have commercial value is tobacco. The motivation of farmers as farm managers is defined as a condition that encourages farmers to do farming activities, namely cultivating tobacco plants. This study identified factors that influence the motivation of farmers to grow tobacco in Suboh Village, Suboh Subdistrict, Situbondo Regency. The location of the study was determined purposively with a sample of 20 respondent. The data were analyzed by using multiple regression techniques with variables of age, education, experience, number of family members, production cost and income. The result showed that education, experience and number of families influenced the motivation of farmers in tobacco cultivation in Suboh Village.